KONTROVERSI KEDUDUKAN ‘ASHABAH DALAM HUKUM WARIS ISLAM MENURUT MADZHAB SYI’AH ITSNA ‘ASY‘ARIYYAH - A. Hasyim Asy’ari (Asy-Syari'ah, 2014)
In Islamic inheritance law system, ulama agreed on the distribution of waris as an ‘ashabah, especially among Sunni. However, it is different from the opinions of ulama among Syi’ah Itsna ‘Asy‘ariyyah which stated that ‘ashabah is out part from the Islamic inheritance law system. In determining the law, ulama Syi’ah Itsna ‘Asy‘ariyyah refers to the Koran, Hadith, and the consensus of the ulama (ijma), and the thought by different ways and methodologies with Sunni. Ulama Syi’ah Itsna ‘Asy‘ariyyah has understood ‘ashabah with their own understanding. They said that ‘ashabah (the residual) is only given to a group of men from tirkah given to ‘ashabah al-furudl, they thought that the residual must be returned to all thabaqat certain groups. Therefore, ulama Syi’ah Itsna ‘Asy‘ariyyah were denying the extance of ‘ashabah In the Islamic inheritance law system. Based on the issue, this paper try to explain the understanding of  ulama Syi’ah Itsna ‘Asy‘ariyyah in determining the law, especially in field of ‘ashabah.